Self-efficacy in Job Preparation for Undergraduate Psychology Students in Palembang City - Asiawatie Sulastri; Edison Wahidin (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
In theory, the world of work greatly influences work readiness, one aspect of which is self-confidence, which shapes work readiness through an individual's belief in their abilities and potential. For student success in all types of desired work, work readiness is required using the potential capital and abilities of the students themselves, including Strata-1 (S1) Psychology students. The research sample was 99 Strata-1 (S1) students in the Palembang area. The sampling technique used was non-probability sampling with the snowball sampling method. The measuring instruments used in the research are self-efficacy and work readiness measurements, which are obtained through the adaptation process. The data obtained by researchers was then analyzed using regression analysis and Fisher Z transformation. As a result of the analysis carried out, it was found that there was a positive and significant relationship between self-efficacy and work readiness and there were differences in the relationship between self-efficacy and work readiness in students. The acceptance of the hypothesis in this research shows that student self-efficacy is related to work readiness. The higher the self-efficacy, the better the student's work readiness and conversely, the lower the self-efficacy, the lower the student's work readiness.